Platelet-derived extracellular vesicles may contribute to the hypercoagulable state in preeclampsia. (November 2021) - Alasztics, Bálint; Kovács, Árpád Ferenc; Molvarec, Attila; Koller, Ákos; Szabó, Gábor; Fekete, Nóra; Buzás, Edit Irén; Pállinger, Éva; Rigó, János
Highlights: There is strong evidence of platelet activation in preeclampsia. Tissue factor positive platelet-derived extracellular vesicles may contribute to the hemostatic disturbances of preeclampsia. Extracellular vesicular molecular markers show different distribution than the same markers on whole platelets. Abstract: It has previously been shown that preeclampsia is associated with disturbed hemostasis and that extracellular vesicles (EVs) play important role in the regulation of hemostatic homeostasis. Thus, we hypothesized that the altered procoagulant characteristics of circulating platelet-derived EVs may contribute to the disturbed hemostasis in preeclampsia. Using multicolor flow cytometry, we have analyzed both tissue factor expressing procoagulant EVs and platelet-derived EV subpopulations derived from resting and activated thrombocytes by examining them in plasma samples of preeclamptic patients and pregnancy-matched healthy individuals. Compared to pregnancy-matched healthy individuals in preeclamptic patients a significantly (p < 0.05) higher ratio of Annexin-V positive activated platelets and a higher number of CD142 + tissue factor bearing procoagulant EVs were found, whereas the absolute amount of circulating CD41a + platelet-derived EVs and CD62P + /CD41a + EVs produced by activated thrombocytes was significantly lower in the plasma of preeclamptic women. In the plasma samples, there was no significant difference in the amount of CD63 + platelet-derived EVs. We propose that increased platelet activation and tissue factor expression of platelet derived extracellular vesicles may contribute to the hypercoagulable state observed in preeclampsia.